Effect of Lactiplantibacillus plantarum cell-free culture on bacterial pathogens isolated from cystic fibrosis patients: in vitro and in vivo studies - Abán, Carla Luciana; Orosco, Silvia; Argañaraz Aybar, Julio Nicolás; Albarracín, Leonardo; Venecia, Analía; Perret, Liliana; Ortiz Mayor, Sonia; Nishiyama, Keita; Valdéz, Juan Carlos; Kitazawa, Haruki; Villena, Julio; Gobbato, Nadia (Frontiers in Microbiology, 2024)
The aim of this work was to investigate the effect of the cell free supernatant of Lactiplantibacillus plantarum ATCC ® 10241 TM on the capacity of Pseudomonas aeruginosa strains isolated from cystic fibrosis (CF) patients to form biofilms. In addition, the study evaluated in vivo the ability of the cell free supernatant to modulate inflammation and reduce lung damage in mice infected with the P. aeruginosa strains or challenged with P. aeruginosa and Streptococcus milleri group (SMG). Results showed that CF-derived P. aeruginosa strains can infect the respiratory tract of adult mice inducing local inflammation and lung damage. The severity of the infection is exacerbated when P. aeruginosa is administered with SMG. Of note, the nebulization with the cell free supernatant of L. plantarum induced beneficial effects in the respiratory infection and inflammatory response induced by P. aeruginosa alone or with SMG. Reduced bacterial loads and lung damage were observed in supernatant-treated mice compared to controls. Although further mechanistic studies are necessary, the results show that the cell free supernatant of L. plantarum ATCC ® 10241 TM is an interesting adjuvant alternative to treat P. aeruginosa respiratory infections and superinfections in CF patients.